Enantioselective Installation of Quaternary Centers in Cyclic Oxonitriles. Issue 30 (9th September 2015) - Gunes, Yakup; Arcelik, Nejat; Sahin, Ertan; Fleming, Fraser F.; Altundas, Ramazan
Abstract: Quaternary centers are rapidly and selectively installed in a series of seven‐membered and bridged cyclic oxonitriles through conjugate addition of an alkoxide to chloroalkenenitriles, followed by a Claisen rearrangement. Using this strategy, the stereogenic information of the carbinol in secondary allylic alcohols is transferred to the newly generated quaternary center. Experimentally, the sequence rapidly gives alkyl cyanocycloheptanones and bicycloalkanonecarbonitriles in good yield and with high selectivity, in a single synthetic operation. Abstract : This strategy allows the transfer of the stereogenic information of secondary allylic alcohols first to an alkoxyalkenenitrile intermediate, and then to a quaternary center through a Claisen rearrangement. This represents an easy method for the installation of a quaternary center in cyanocycloheptanones and bicycloalkenecarbonitriles in good yield and high selectivity, in a simple synthetic operation.